The associations between serum carotenoids and hyperuricemia among U.S. National Health and Nutrition Examination Survey - Hong He; Ping Li; Haokun Huang; Yanlin Zeng; Min Zhang; Zhibing Chen; Shiqi Huang; Fangfang Zeng; Hui Ge (BMC Public Health)
Abstract Background Hyperuricemia is a risk factor for various metabolic disorders. We aimed to investigate the association between serum carotenoid levels and hyperuricemia using data from the National Health and Nutrition Examination Survey (NHANES). Methods We conducted a cross-sectional analysis utilizing data from three specific NHANES cycles (2003–2004, 2005–2006, 2017–2018), containing the most complete serum carotenoid data from 12,253 participants aged 20 years and older. Serum carotenoids were quantified using high-performance liquid chromatography, while hyperuricemia was defined as serum uric acid levels ≥ 416 μmol/L (7.0 mg/dL) in men and ≥ 357 μmol/L (6.0 mg/dL) in women. Multivariable logistic regression models were employed to assess the relationship between carotenoids and hyperuricemia. Results The mean age of participants was 50.1 ± 18.7 years, with a hyperuricemia prevalence of 20.5%. Higher serum carotenoids were associated with a lower prevalence of hyperuricemia, with each 1-unit increase in total carotenoids being inversely associated with hyperuricemia (odds ratio [OR] = 0.77, 95% confidence interval [CI]: 0.72–0.82) in multivariable analyses. Compared to participants with the lowest quartile, reduced ORs for hyperuricemia odds were observed for those with the highest quartile for total carotenoids (0.55 [0.47–0.64]), α-carotene (0.60 [0.52–0.71]), β-carotene (0.56 [0.48–0.65]), β-cryptoxanthin (0.58 [0.49–0.67]), trans-lycopene (0.75 [0.65–0.87]), cis-lycopene (0.83 [0.65–1.06]), total-lycopene (0.75 [0.64–0.87]), and lutein + zeaxanthin (0.66 [0.57–0.77]). Subgroup analyses indicated stronger associations among younger individuals, women, and those without any history of diabetes or cardiovascular disease. Conclusions Higher serum carotenoid levels are associated with reduced odds of hyperuricemia. These results underscore the potential role of carotenoids in managing hyperuricemia and its related health complications.